2022
DOI: 10.1007/s00382-021-06098-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of resolution on the atmosphere–ocean coupling along the Gulf Stream in global high resolution models

Abstract: We have investigated the horizontal resolution dependence of the ocean–atmosphere coupling along the Gulf Stream, of simulations made by six Global Climate Models according to the HighResMIP protocol, and compared it with reanalysis and remote sensing observations. Two ocean–atmosphere interaction mechanisms are explored in detail: The Vertical Mixing Mechanism (VMM) associated with the intensification of downward momentum transfer, and the Pressure Adjustment Mechanism (PAM) associated with secondary circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 92 publications
2
6
0
Order By: Relevance
“…Precipitation was overestimated in the models for the winter and underestimated for the summer, while temperature and potential evapotranspiration were found to be overestimated in the summer and underestimated in the winter. The results about the bias match similar results in other studies (e.g., Moreno‐Chamarro et al., 2021, 2022; Squintu et al., 2021; Tsartsali et al., 2022; Zhao, 2020, 2022). We did not investigate the sensitivity of the biases on hydrologic simulations and future work should strive to incorporate this type of analyses.…”
Section: Discussionsupporting
confidence: 91%
“…Precipitation was overestimated in the models for the winter and underestimated for the summer, while temperature and potential evapotranspiration were found to be overestimated in the summer and underestimated in the winter. The results about the bias match similar results in other studies (e.g., Moreno‐Chamarro et al., 2021, 2022; Squintu et al., 2021; Tsartsali et al., 2022; Zhao, 2020, 2022). We did not investigate the sensitivity of the biases on hydrologic simulations and future work should strive to incorporate this type of analyses.…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that at least eddy-permitting ocean resolution and comparable atmosphere resolution are required for a reliable storm track simulation, subjected to correct model physics and other feedbacks. This finding is consistent with a previous study (Tsartsali et al, 2022) that reported similar inferences for the Gulf Stream region.…”
Section: Model's Skill For Wind and Its Extremes (Storm Track Density)supporting
confidence: 94%
“…Most of the global climate models participating in CMIP5 activities have a nominal resolution of about 150 km in the atmosphere and 1° in the ocean (Eyring et al., 2016; T. Rackow et al., 2018; Taylor et al., 2012) providing a reasonable trade‐off between computing time and model complexity. Various studies noted the improvement in the model performance (either global or regional) by increasing the atmospheric or oceanic resolution over most parts of the world (Bador et al., 2020; de la Vara et al., 2020; Güttler et al., 2015; Hack et al., 2006; Mishra et al., 2021; Moreno‐Chamarro et al., 2022; Strandberg & Lind, 2021; Tsartsali et al., 2022). Strandberg and Lind (2021) show notable improvement in high or moderate precipitation intensities over Europe after increasing atmospheric resolution (downscaling CMIP5 with a regional climate model).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the ocean model resolution may also affect the pathways and adjustment processes in the transient response of the AMOC to the water hosing (e.g., Mecking et al 2016;Swingedouw et al 2022). Higher resolutions in both the atmosphere and the ocean influence the air-sea interactions, ultimately affecting precipitation impacts, especially over coastal areas or complex topography (e.g., Tsartsali et al 2022;Bellucci et al 2021;Haarsma et al 2019). Reproducing these experiments with higher model resolution and in different models could thus help us gain further insights and advance the results of this study.…”
Section: Discussionmentioning
confidence: 99%